Role of cancer stem cells in pancreatic ductal adenocarcinoma - Sergeant, Gregory; Vankelecom, Hugo; Gremeaux, Lies; Topal, Baki (Nature reviews. Clinical oncology, 2009)
With greater understanding of the biology of pancreatic cancer a role for cancer stem cells is becoming clear. The authors of this Review discuss the current knowledge on pancreatic cancer stem cells and their potential use as targets in therapeutic regimens. As our understanding of pancreatic cancer evolves, evidence is growing to support a role for cancer stem cells in this devastating disease. Cancer stem cells constitute a distinct subpopulation in the tumor and are considered to drive both tumorigenesis and metastasis; these cells are thought to be highly resistant to standard treatment modalities. Here we review the current knowledge on pancreatic cancer stem cells and the implementation of cancer stem cell markers as prognostic or predictive biomarkers. We also discuss prospects for the use of cancer stem cells as targets for future therapeutic regimens in pancreatic cancer. Key Points Conventional chemotherapy and radiotherapy affect rapidly dividing pancreatic cancer cells but fail to target cancer stem cells that drive tumorigenesis and metastasis Pancreatic cancer stem cells with either a CD44 + CD24 + ESA + or a CD133 + phenotype have been identified from primary human pancreatic ductal adenocarcinoma The metastatic potential of pancreatic ductal adenocarcinoma seems to be determined by a subpopulation of CD133 + cells that co-express CXCR4 Developmental signaling pathways that regulate self-renewal and cell fate in normal stem cells are also involved in pancreatic cancer stem cells and might serve as novel biomarkers and therapeutic targets Any treatment designed to eradicate pancreatic cancer needs to eliminate all cancer stem cells from the tumor The success of any approach that targets pancreatic cancer stem cells will depend upon further identification and characterization of normal pancreatic stem cells, cancer stem cells and the surrounding tumor stroma